Presence, feeding and health status of collared doves (Streptopelia decaocto Friv. 1838) on animal breeding farms - Varga, Sándor; Juhász, Lajos (Acta Agraria Debreceniensis, 2006)
In the course of our examinations we were determining the gender of collared doves (Streptopelia decaocto) feeding at animal breeding farms by biometric data. We were estimated their nourishment and necropsies were carried out.We compared the results of the nutrition analysis with similar data of collard doves feeding at agricultural areas.We analyzed the crop and gizzard content and recorded the body proportions of collard doves that were captured between December of 2004 and August 2005. In the course of the necropsy examinations we did parasitological, bacteriological examinations as well as examinations for the detection of Newcastle disease. In the course of the gender analysis of the collard doves that were collected at animal breeding farms, both the wing length and the length of the third quill-feather has shown a significantly greater value in the case of males (p>0.05).From the orts found in the crop and gizzard it has been stated that the feed consumed the most was corn (80.77% m%). The collared doves consumed much less other cereal seeds (wheat 0.82%, barley 1.26%).In the course of the necropsy examinations done in the Veterinary Institute of Debrecen, the birds proved to be free of parasites, and the results of the Salmonella and Newcastle disease analysis were negative as well. E. coli bacteria had been detected in the liver of not more than three birds.